EFEKTIVITAS MODEL PEMBELAJARAN PJBL BERBASIS STEAM DENGAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF SISWA MATERI SIMETRI LIPAT - Puspita Ramadhani, Novicka; Rosmiati; Erlin Ladyawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the STEAM-based Project-Based Learning (PjBL) model with a Deep Learning approach in improving students’ reflective thinking skills on the topic of fold symmetry in elementary school. The research employed a descriptive quantitative method with a pretest–posttest design. The results indicate that the implementation of this model enhances students’ reflective thinking skills and creates a more meaningful, active, and student-centered learning environment. In addition, the model supports the development of critical and creative thinking as well as students’ cognitive and metacognitive abilities. Therefore, the integration of PjBL, STEAM, and Deep Learning is considered effective in improving higher-order thinking skills in elementary education.